The Impact of COVID-19 on Intoxication Pattern by Drugs of Abuse in Egypt - Aboubakr, Heba Mohamed; Kotb, Nadia Abd El Monem; Shaban, Fatma; Elattar, Hanaa Mohamed Samir; Shalaby, Ezzeldin (International Journal of Medical Toxicology and Forensic Medicine, 2023)
Background: Drug abuse is considered a global and growing problem worldwide. Emergency medical care is required for acute intoxication, which adds to the threat of COVID-19. This study aims to evaluate the effect of the COVID-19 pandemic on the pattern of acute toxicity in drug abuse patients admitted to National Environmental and Clinical Toxicology and Research Center (NECTR), Cairo University. Methods: This comparative study included 978 cases admitted to NECTR during 12 months before the COVID-19 pandemic (2018-2019) and 12 months during the pandemic (2020-2021). Results: The number of cases during the pandemic was lower than before; adults and men predominate in both periods. During the pandemic, cannabis, heroin, opium, and alcohol showed a mild increase, while the new synthetic drugs, tramadol, and pregabalin, showed a mild decrease. A significant increase in discharges and a decrease in intensive care unit (ICU) admissions were observed during the pandemic. Besides, more oxygen (O2) therapy was required, and more cases died on mechanical ventilation. The worst outcome was associated with old age, male gender, heroin and opium toxicity, and the highest score of poisoning severity. Conclusion: The COVID-19 pandemic had a definite reforming effect on the pattern of intoxication by drugs of abuse in NECTR, Egypt.